Analisis Faktor-Faktor yang Mempengaruhi Tingkat Kemiskinan Provinsi Bangka Belitung Tahun 2010 - 2020 - Atika, Nur; Jalunggono, Gentur (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2022)
This study aims to analyze the impact of education on the growth of the poor population in Bangka Belitung Province in the 2010-2020 period. The data used in this study are secondary panel data taken from BPS (Central Statistics Agency) from seven districts/cities in Bangka Belitung including Bangka Regency, Belitung Regency, West Bangka Regency, Central Bangka Regency, South Bangka Regency, East Belitang Regency, and Pangkalpinang City in 2010-2020 using the variable growth of the poor population as the dependent variable, while the independent variables used are Gross Domestic Regional Product (GDRP), per capita expenditure, average length of schooling, and also the open unemployment rate. After Chow and Hausman test, it can be seen that the best research model for this research is the Fixed Effect Model method. From this research, it is known that the dependent variables have a positive and significant influence on the dependent variable. Meanwhile, if based on the results of individual tests, the average length of schooling and the open unemployment rate have a significant effect on the dependent variable and no significant effect is found on the GDRP and per capita expenditure variables on the dependent variable.